Encyclopedia of early Christianity - Ferguson, Everett, 1933-; McHugh, Michael P.; Norris, Frederick W. 1941- (New York, NY Garland, 1999)
Includes bibliographical references and index.
Keywords: Church history -- primitive and early church, ca. 30-600 -- encyclopedias